Associations of mental health with vaccination readiness in informal caregivers and the vaccination status of their care recipients during the Covid-19 pandemic – A cross sectional analysis - Sanftenberg, Linda; Bader, Felix; Rottenkolber, Marietta; Sebastiao, Maria; Kühlein, Thomas; Eidenschink, Christine; Gágyor, Ildikó; Wildgruber, Domenika; Hausen, Anita; Janke, Christian; Hoelscher, Michael; Teupser, Daniel; et al. (Vaccine, 2024)
Introduction: Vaccinations are important for informal caregivers and their care recipients. Mental health problems are common among care givers. The aim of this study was to investigate vaccination readiness in informal caregivers and associations with mental health issues. Associations between vaccination readiness in informal caregivers and the vaccination status of their aged care recipients were examined. Methods: Within the multicenter prospective registry study ‘Bavarian ambulatory Covid-19 Monitor (BaCoM) ‘, informal caregivers were asked for symptoms of depression (PHQ-9), burden of caretaking (BSFC-s), psychological antecedents of vaccination readiness (5C model) and previous Covid-19 infections of their care recipients. The vaccination status against Covid-19, seasonal influenza and pneumococcal disease was determined via vaccination certificates. Data analysis was performed using ordinal regressions and Mann-Whitney-U tests. Results: Data of n = 91 informal caregivers, associated with n = 84 care recipients were collected. Symptoms of depression were associated with reduced vaccination readiness (Calculation: p = 0.026, OR = 1.18), as well as the perceived burden of caretaking (Confidence: p = 0.006, OR = 0.88). A previous Covid-19 infection of the care recipients was associated with decreased vaccination readiness of informal caregivers (Median (Q1–Q3) Confidence: 5.0 (4.5–6.0) vs. 4.0 (3.0–5.0); Calculation: 5.0 (3.0–6.0) vs. 4.0 (1.0–5.0)). The vaccination status of the care recipients interrelated significantly with vaccination readiness of their informal caregivers (Confidence: p < 0.001; Complacency: p < 0.01; Constraints p < 0.05). No significant interrelations between vaccination readiness and the vaccination status against seasonal influenza or pneumococcal disease occurred. Conclusion: Mental health issues of informal caregivers seem to be associated with the actual vaccination status against Covid-19 in their care recipients. Target group specific counselling as well as an active involvement of informal caregivers in shared decision-making processes can be of relevance, but even more attention should be paid to the protection of mental health for informal caregivers. Trial registration number: German Register of Clinical Studies DRKS 26039.
CRIS-Team Scopus Importer:2024-09-06
Keywords: COVID-19; Informal caregivers; Long-term care; Mental health; Vaccination readiness